PENGARUH MEDIA PEMBELAJARAN BERBANTUAN FILM DOKUMENTER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS DI KELAS VIII B SMP NEGERI 1 SINDUE - Muliana, Muliana (Katalogis, 2017)
This research aimed to analyze the influence of media study used documentery film concerning the result of students learning at social subject at class VIII B at SMP Negeri 1 Sindue. This experimental research used the design of quacy experiment. The population of this research was from eighth grade students of SMP Negeri 1 Sindue which consist of class VIII B as experimental class and class VIII C as control class. The sampling technique used is random sampling techniques. Independent variable in this research was documentery film and dependent variable were the students learning outcomes at social subject. The technique of data collection used test. The validation and reliability counted using excel. The requirenmets using SPSS 19.00 aid using covering normality test by Kolmogorov-Smirnov and homogeneity test used Levene Test. Hypothesis test used t-test with significantly level 0.05. The result of the research indicated the achievement of mean or average to 78,76 for the experimental class by using documentery film, while mean of control class do not used the media only get 54,28 or didnot reach the minimum standard of 70. Based on statistical test result, t-test indicated that the value of sig or p about 0,000 compared smaller of 0,025. In conclusion, the result of the reasearch both experimental class and control class did not same or different actually.